2001
DOI: 10.1203/00006450-200110000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Tobacco Smoking and Lung Epithelium-Specific Proteins in Amniotic Fluid

Abstract: The bronchiolar 16 kD Clara cell secretory protein (CC16) and the alveolar surfactant-associated protein A (SP-A) are secreted in the amniotic fluid (AF), where they reflect the growth and the maturity of the fetal lung. To evaluate the possible effects of in utero tobacco smoke exposure upon infant bronchoalveolar epithelium function and maturity, CC16 and SP-A levels were determined in AF obtained at term (36 -41 wk) from 28 nonsmoking, 18 smoke-exposed, and 28 smoking mothers with uncomplicated pregnancies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…However, Wuenschell et al (35) reported significant increases in the expression of SP-A and -C mRNAs in a murine developing lung explant model. Hermans et al (11) did not find any significant differences in amniotic fluid SP-A levels at full term in smoke-exposed vs. non-smoke-exposed pregnancies. The conflicting results in these studies are likely to be related to differences in the models used (species and stage of lung development), duration of nicotine exposure (acute vs. chronic), whether smoke or nicotine was used as a challenge, and the end points, for example, whether phospholipid synthesis, secretion, or total pool size was examined.…”
Section: Discussionmentioning
confidence: 86%
“…However, Wuenschell et al (35) reported significant increases in the expression of SP-A and -C mRNAs in a murine developing lung explant model. Hermans et al (11) did not find any significant differences in amniotic fluid SP-A levels at full term in smoke-exposed vs. non-smoke-exposed pregnancies. The conflicting results in these studies are likely to be related to differences in the models used (species and stage of lung development), duration of nicotine exposure (acute vs. chronic), whether smoke or nicotine was used as a challenge, and the end points, for example, whether phospholipid synthesis, secretion, or total pool size was examined.…”
Section: Discussionmentioning
confidence: 86%
“…A randomized, placebo-controlled clinical trial of a single dose of rCC16 delivered by the intra-tracheal route to premature infants with respiratory distress syndrome having low CC16 levels in tracheal aspirate fluid (TAF) samples showed that this therapy was well tolerated, and resulted in a significant reduction in leukocyte counts and a strong trend towards reduced IL-6 levels in TAF samples 62 . Interestingly, prenatal exposure to CS is associated with decreased expression of CC16 in fetal rat lungs 67 , but this correlation has not been confirmed in human neonates 68 .…”
Section: Club Cell Protein-16 (Cc16)mentioning
confidence: 96%
“…However, there are reports that suggest that maternal smoking does not influence lung surfactant proteins of exposed neonates. For example, neonates from mothers who smoked during pregnancy did not show reduced levels of SP-A according to amniotic fluid measurements 24. There is also a report indicating that smoking in healthy individuals increases levels of SP-A when measured in serum 25.…”
Section: Discussionmentioning
confidence: 99%